Dystrophic calcinosis cutis in autosomal recessive dystrophic epidermolysis bullosa - Bhari, Neetu (BMJ Case Rep, 2019)
A 6-year-old girl presented with a history of blistering and scarring in trauma-prone areas. On examination, calcium deposits were seen on bilateral palms and soles within her non-healing wounds. Clinical, genetic and radiological evaluation confirmed the diagnosis of autosomal recessive dystrophic epidermolysis bullosa with dystrophic calcification. The patient was started on topical 10% sodium thiosulfate for her calcinosis cutis. Identification and management of dystrophic calcification are important as it impairs wound healing.